If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(18 + -6y) + -3y = -24 (18 * 2 + -6y * 2) + -3y = -24 (36 + -12y) + -3y = -24 Combine like terms: -12y + -3y = -15y 36 + -15y = -24 Solving 36 + -15y = -24 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -15y = -24 + -36 Combine like terms: 36 + -36 = 0 0 + -15y = -24 + -36 -15y = -24 + -36 Combine like terms: -24 + -36 = -60 -15y = -60 Divide each side by '-15'. y = 4 Simplifying y = 4
| 9=3(k-1)+k | | y=cos(2y) | | 2l=21 | | 7x-112=0 | | 21=6n | | 5X+(3X-20)=500 | | b-2b=15 | | 3x-105=0 | | f(y)=cos(2y) | | -3x+6(5x-2)=-6 | | hot+girl= | | 8(x-2)=5x+11+3x | | 3x+3(x+15)=15 | | 4n=0.56 | | x^2y-9y+3x-27=0 | | 5(x+-4)+2x=14 | | y=4(1.666666667)+6 | | 5x-15=20-2x | | 10cos(x)+sin^2(x)=0 | | mx+nc=y | | 2x^4-8=0 | | 2x^5-8=0 | | (-25)x(-13)= | | -25x-13= | | 8.3(x-31)=-37.35 | | 2z^2+7z+5=6z^2 | | (logx)6561=8 | | 9x+18=5x+38 | | x+4(-1)=8 | | 7x-4(-2x+7)=-193 | | X+7=3(x+7)-19 | | R=176-0.8x |